Consenso e colaboração em procedimento de apuração de ato de improbidade administrativa - Vasconcelos, Agtta Christie Nunes (2019)
Public morality is, among the constitutional administrative principles, the most discussed in Brazilian reality, at which time it is identified the scrapping of public finances and crimes against public patrimony have been punished. The traditional impunity of criminal offenses against the public administration could be modified through the mechanisms present in the Law to Combat the Criminal Organization, which, although it had not been published with this primary purpose, gave prominence to the awarded collaboration as an important probative element. Even in view of the success provided by the new tools, criminal prosecution presents three main obstacles: the delay, due to the existence of privileged forum of some processed; deficiency of compensation for values deviating from public administration; and the difficulty of crime prevention, since the criminal response is subsequent to the effective loss to the public administration. In addition to the difficulties, the penal sanction should have an exceptional application in the legal system, including the existence of a more extensive and adequate judicial measure to sanction all types of illicit acts against the public administration, which is the administrative improbity action instituted through Law 8.429 / 1992. The aforementioned action, which is genuinely Brazilian, encompasses the peculiarities of the behavior that threatens administrative morality, but it is inexpressive, among other reasons, due to its probative deficiency and prohibition of judicial negotiation. Thus, the applicability of the consensus and collaboration in the actions of administrative improbity must be analyzed before the legal system in force, so that the compatibility, benefits and losses are evaluated.